M. G. Meerovich. From Unpublished Works - Lidin, Konstantin (project baikal, 2019)
The article reviews the methodological aspect of Mark Grigorievich Meerovich’s creative legacy. It shows the evolution of the scientist’s views, from V. A. Pavlov’s practical school, through G. P. Shchedrovitsky’s circle and Foucault’s mainstream historiosophical tradition. During the last years of his life, M. G. Meerovich started implementation of a fundamental work on updating of interdisciplinary methodological basis of architecture. His sudden death terminated this substantial and promising work.
Keywords: architecture; theory; methodology; M. G. Meerovich; history; biography